Compressive deformation behavior of AZ31 alloy at 21K: an in-situ neutron diffraction study. (1st March 2023) - Gong, Wu; Kawasaki, Takuro; Zheng, Ruixiao; Mayama, Tsuyoshi; Sun, Binxuan; Aizawa, Kazuya; Harjo, Stefanus; Tsuji, Nobuhiro
Abstract: Deformation behavior during uniaxial compression at 21 K and 298 K in a commercial AZ31 magnesium alloy was studied by in-situ neutron diffraction. Decreasing the deformation temperature resulted in a slight increase in yield stress (115 MPa →139 MPa), but a remarkable enhancement in both the fracture stress (365 MPa → 551 MPa) and fracture strain (12.8%→16.5%). The low temperature sensitivity of the {10 1 ¯ 2} extension twinning which governed the macroscopic yielding led to the slight increase in yield stress. At 21K, basal slip was suppressed, while the extension twinning was promoted resulted in higher twin volume fraction. In the late stage of deformation, the {10 1 ¯ 1}-{10 1 ¯ 2} double twinning was suppressed, which is considered to be the reason to delay the fracture at 21 K. Graphical abstract: Image, graphical abstract